(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2019)
The article actualizes the problem of mastering the Method of Event-Action Analysis by the students of theatrical schools. The author of the article proposes the propaedeutical practical stage of the Method application. The stage makes abstract and specific structures meet in the creative analyses of very different texts of culture like paintings, landscapes, historical events and even the laws of nature.The article offers the examples of creative works of the students of Novosibirsk drama school in application the Method of Event-Action Analysis to cultural texts.